On the Influence of American Romanticists upon W. Faulkner - Pavilionienė, Marija Aušrinė (Literatūra, 1973)
The paper analyses the creation of William Faulkner in the light of the heritage of the early American romanticism, transcendentalism and the late romanticism. The author considers the originality of W. Faulkner to be due to his adoption and reinterpretation of the named traditions of American fiction. Thus the common core in the creation of F. Cooper, transcendentalists and W. Faulkner is their antibourgeois orientation and glorifying of Nature. Man, his inner world, his interpretation of the outer world make the centre of the artistic analysis in the creation of both N. Hawthorne and W. Faulkner. Common themes (the place of the past in the present of man, his moral imperfection) bring the two authors together. What relates closely H. Melville and W. Faulkner is their ability to create strong, integral characters driven by the only and all-absorbing passion. Besides, W. Faulkner made a skillful use of "the three types of cognitive consciousness", developed by H. Melville.
Keywords: -